Effect of an Action-Research nutrition intervention on the Global Diet Quality Score of Colombian adolescent (2023)
ABSTRACT: Strategies to address the nutritional needs of adolescent girls and young women often focus on supplementation. In this study, an action-research approach involving a nutrition education and entrepreneurship intervention was carried out among adolescent girls and young women in poor neighborhoods of Medellín, Colombia. The intervention group significantly increased its intake of several nutrients, including energy, protein, total fat, saturated fat, monounsaturated fat, polyunsaturated fat, cholesterol, dietary fiber, calcium, zinc, and vitamins A, B2, B3, B9, and C. A significant increase was observed in the intake of the Global Diet Quality Score (GDQS) healthy food groups (other fruits, other vegetables, legumes, high-fat dairy products), accompanied by a decrease in the consumption of some unhealthy food groups (sweets and ice creams). A multivariate regression controlling for age, socioeconomic status, occupation, Household Hunger Scale, mean probability of adequacy, physical activity, and body self-perception showed that the nutrition intervention improved the total GDQS by 33% in the intervention group—a substantial improvement notwithstanding the study group’s precarious social and economic conditions. We conclude that nutrition education and entrepreneurship models based on this approach may improve the dietary profile of this population and reduce future pressures from nutrition-related chronic diseases.